Plano de Gerenciamento Integrado de Resíduos Sólidos de Campina do Monte Alegre, SP - Boniolo, Vinicius Rainer (Universidade Federal de São Carlos, 2019)
It was proposed here to characterize the municipal solid waste collection system of the municipality, to diagnose the solid waste generated or administered containing the origin, volume and characterization of waste, including related environmental liabilities, to understand the possibilities of environmentally appropriate final destinations, identify consortium or shared solutions with other generators, propose preventive and corrective actions to be performed in situations of mismanagement or accidents, and propose routes for the collection of domestic solid waste and for selective collection. Thus, with the theoretical framework raised and the various results obtained in this work, an important theoretical tool was developed so that the Municipal Plan of Integrated Solid Waste Management of Campina do Monte Alegre will be put into practice in the near future. This research will certainly help the fulfillment of the propositions foreseen over the next years, however, it is known that the implementation of this Plan will depend on political articulations of the municipal public management in question. Its implementation will be of great importance, as it will bring positive consequences, leading the municipality to social inclusion and will significantly reduce the environmental impacts caused by improper disposal of waste. Reflections of the results of this work will be achieved over the years, that is, in the medium or long term, as there are specific goals to be met in different sectors of the city hall, with different schedules. Finally, it can be stated that the management plan will contribute to the municipality in question to comply with the Law, and to broaden respect for public health, technical, environmental, social and administrative issues
Integrated Solid Waste Management Plan of Campina do Monte Alegre, SP
Keywords: Gestão municipal; Resíduos sólidos; Destinação adequada; Geradores; Municipal management; Municipal waste; Proper destination; Waste generators; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::POLITICA E PLANEJAMENTO GOVERNAMENTAIS; ENGENHARIAS::ENGENHARIA SANITARIA